Prediction of entropy and Gibbs free energy for nitrogen. (20th July 2019) - Jia, Chun-Sheng; Zhang, Lie-Hui; Peng, Xiao-Long; Luo, Jian-Xin; Zhao, Yu-Long; Liu, Jian-Yi; Guo, Jing-Jing; Tang, Lian-Dong
Graphical abstract: Highlights: We present efficient closed-form representations of molar entropy and Gibbs free energy for pure substances. Present molar entropy and Gibbs free energy prediction models are only involving three molecular constants. We excellently predict molar entropies and Gibbs free energies for the N2 gas. Abstract: Nitrogen (N2 ) is widely used in oil and gas industry. We report two new efficient closed-form representations for the molar entropy and Gibbs free energy of pure gaseous substances. A comparison of the predicted and experimental values shows that the molar entropies and Gibbs free energies of N2 can be excellently predicted in the temperature range of 100–6000 K. The present entropy and Gibbs free energy prediction models only require the experimental values of three molecular constants and are away from the utilization of a great number of experimental spectroscopy data.